Analysing cinematic discourse using conversation analysis. (December 2016) - Chepinchikj, Neda; Thompson, Celia
Abstract: The following paper examines how a conversation analysis (CA) approach to the investigation of spoken dialogue can be applied to analysis of the verbal and non-verbal (prosodic and paralinguistic) features of film discourse. In doing so, we wish to make a valuable contribution to the debate in the field between 'pure' (seeSchegloff, 1988 ;Emmison, 1993 ) and 'applied' CA scholars (e.g.ten Have, 2007 ). Researchers belonging to the former grouping argue that CA should only be used to investigate naturally occurring language use (i.e. spontaneous language use), while those who position themselves as 'applied' CA scholars maintain that it is an approach that can be applied to institutional and semi-scripted instances of spoken dialogue. We begin by outlining the principles of CA and the type of data and contexts in which it has been used to analyse spoken interaction in previous research; we then analyse and discuss findings from our own study into the verbal and non-verbal features of segments of film discourse. These segments comprise selected interactions that occur in three different scenes from three different films by Woody Allen ("Husbands and Wives", 1992; "Melinda and Melinda", 2004 and "You Will Meet a Tall Dark Stranger", 2010). These interactions have been transcribed using CA conventions and then analysed in terms of four key conversational features that have been identified by CA scholars: turn-taking, adjacency pairs, gaps and overlaps. Our findings indicate that the interactants in our study do indeed make use of these conversational features in their spoken dialogues and that they are purposeful and meaningful. We conclude therefore that CA offers a valuable tool for examining key verbal and non-verbal features of film dialogue and paves the way for further analyses of this kind.